Rhodium-Catalyzed Intermolecular [5+1] and [5+2] Cycloadditions Using 1,4-Enynes with an Electron-Donating Ester on the 3-Position - Schienebeck, Casi M.; Song, Wangze; Smits, Angela M.; Tang, Weiping (Synthesis, 2015)
Various 3-acyloxy-1,4-enynes could be employed in rhodium-catalyzed intermolecular [5+1] and [5+2] cycloadditions with CO or alkynes, respectively. The rate of these cycloadditions could be accelerated significantly by using 1,4-enynes with an electron-donating ester on the 3-position. The scope of rhodium-catalyzed [5+1] and [5+2] cycloadditions were examined by using 1,4-enynes bearing an electron-donating ester.1 Introduction2 Rhodium-Catalyzed Intermolecular [5+2] Cycloaddition3 Rhodium-Catalyzed Intermolecular [5+1] Cycloaddition4 Conclusion
Keywords: catalysis; cycloaddition; rhodium; rings; benzene